The Relationship Between Clean Water Sources, Waste Management, and Availability of Healthy Latrines with the Incidence of Pulmonary TB in Marginal Community - Hasanuddin, Asni; Alwi, Muh Khidri; Dita Ellyana Artha; Aisyah; Ricvan Dana Nindrea; Ardiansah Hasin (PT Inovasi Pratama Internasional, 2023)
Pulmonary TB is a disease that can attack anyone because the source of this disease is very broad, especially in the environmental aspect. These environmental aspects include rubbish, clean water sources, and healthy latrines. The incidence of pulmonary TB in the Minasatene Community Health Center working area is still found. This research aims to determine the relationship between waste management, availability of latrines, and clean water sources with the incidence of pulmonary TB in Minasatene District, Pangkajene Islands Regency. This type of research is a quantitative analytical survey with a cross-sectional study design. The sampling technique used in this research was a simple random technique (Simple Random Sampling) with a sample size of 163 respondents. The results of the research are that there is a relationship between waste management and the incidence of diarrhea with a value of p = 0.006, there is a relationship between clean water sources and the incidence of diarrhea with a value of p = 0.000, there is a relationship between the availability of healthy latrines and the incidence of diarrhea with a value of p = 0.000, there is a need to manage community waste through counseling or outreach organized by the government or private sector.